Pengaruh Emotional Polarity, Argument Quality, dan Presentation Modality Terhadap Perceived Review Helpfulness dan Trust In Muslim Fashion Review pada E-Commerce Shopee - Prasetyo, Denise Natashya; Susilowati, Fitriah Dwi (Jurnal Ekonomika dan Bisnis Islam, 2024)
The development of digital technology makes it easier for consumers to shop online, but raises consumer doubts about the products they want to buy. To overcome this, consumers rely on online reviews. This study examines the effect of differences in emotional polarity, argument quality, and presentation modality on perceived review helpfulness and trust in reviews on Muslim fashion at Shopee E-commerce using ANOVA analysis techniques and simple linear regression tests. The results showed that reviews with emotional mix-neutral, strong argument, and rich modality were more helpful than positive emotional, weak argument, and lean modality. In addition, perceived review helpfulness affects trust in reviews. Marketers can increase perceived review helpfulness by encouraging reviews that consist of positive and negative product details, strong arguments and use high modality.